Evaluation of 5,5’-Oxybis(1,3,7-Trihydroxy-9H-Xanthen-9-One) as an Anticancer Agent Through In Vitro and In Silico Tests - Ayu Nadila Safitri; Aldillah Herlambang; Muhammad Irhash Shalihin; Nurul Pratiwi; Putri Dwi Mulyani; Nania Septiyani; Muktaf Wando Saputra (Indonesian Journal of Chemical Research, 2026)
Breast cancer is among the most common malignancies globally and continues to be a primary cause of cancer-related deaths in women. Modern chemotherapeutic agents often exhibit resistance and lack of selectivity for healthy cells, leading to significant side effects. Consequently, several strategies are essential to overcome resistance and enhance the selectivity and efficacy of chemotherapeutic drugs derived from natural sources. This study investigates the anticancer activity of a new bis-xanthone compound, 5,5'-Oxybis(1,3,7-trihydroxy-9H-xanthen-9-one), in MCF-7 breast cancer cells using a combination of in vitro and in silico approaches. The compound exhibited cytotoxicity against MCF-7 breast cancer cells, with an IC50 value of 30.47 µg/mL. The pharmacokinetic characteristics of bis-xanthone compounds were evaluated using absorption, distribution, metabolism, excretion, and toxicity (ADMET) tests, demonstrating a more favorable profile than that of doxorubicin, a standard anticancer drug.